Interprotein Electron Transfer between FeS‐Protein Nanowires and Oxygen‐Tolerant NiFe Hydrogenase. Issue 27 (6th June 2017) - Rengaraj, Saravanan; Haddad, Raoudha; Lojou, Elisabeth; Duraffourg, Nicolas; Holzinger, Michael; Le Goff, Alan; Forge, Vincent
Abstract: Self‐assembled redox protein nanowires have been exploited as efficient electron shuttles for an oxygen‐tolerant hydrogenase. An intra/inter‐protein electron transfer chain has been achieved between the iron‐sulfur centers of rubredoxin and the FeS cluster of [NiFe] hydrogenases. [NiFe] Hydrogenases entrapped in the intricated matrix of metalloprotein nanowires achieve a stable, mediated bioelectrocatalytic oxidation of H2 at low‐overpotential. Abstract : Wired up : Self‐assembled redox protein nanowires were exploited as efficient electron shuttles for an oxygen‐tolerant hydrogenase. [NiFe] Hydrogenases entrapped in the intricate matrix of metalloprotein nanowires achieve a stable, mediated bioelectrocatalytic oxidation of H2 at low overpotential.